Serotonergic mechanisms of the lateral parabrachial nucleus and cholinergic-induced sodium appetite - Menani, José Vanderlei [UNESP]; Barbosa, S. P.; De Luca, L. A.; De Gobbi, JIF; Johnson, A. K. (Amer Physiological Soc, 2002)
Central cholinergic mechanisms are suggested to participate in osmoreceptor-induced water intake. Therefore, central injections of the cholinergic agonist carbachol usually produce water intake (i.e., thirst) and are ineffective in inducing the intake of hypertonic saline solutions (i.e., the operational definition of sodium appetite). Recent studies have indicated that bilateral injections of the serotonin receptor antagonist methysergide into the lateral parabrachial nucleus (LPBN) markedly increases salt intake in models involving the activation of the renin-angiotensin system or mineralocorticoid hormones. The present studies investigated whether sodium appetite could be induced by central cholinergic activation with carbachol (an experimental condition where only water is typically ingested) after the blockade of LPBN serotonergic mechanisms with methysergide treatment in rats. When administered intracerebroventricularly in combination with injections of vehicle into both LPBN, carbachol (4 nmol) caused water drinking but insignificant intake of hypertonic saline. In contrast, after bilateral LPBN injections of methysergide (4 mug), intracerebroventricular carbachol induced the intake of 0.3 M NaCl. Water intake stimulated by intracerebroventricular carbachol was not changed by LPBN methysergide injections. The results indicate that central cholinergic activation can induce marked intake of hypertonic NaCl if the inhibitory serotonergic mechanisms of the LPBN are attenuated.
Keywords: carbachol; water intake; thirst; salt intake; salt appetite; 5-hydroxytryptamine